2018
DOI: 10.3390/fib6020027
|View full text |Cite
|
Sign up to set email alerts
|

Expression Analysis of Cell Wall-Related Genes in Cannabis sativa: The “Ins and Outs” of Hemp Stem Tissue Development

Abstract: Textile hemp (Cannabis sativa L.) is a multipurpose crop producing biomass with uses in e.g., the textile, biocomposite, and construction sectors. It was previously shown that the hypocotyl of hemp is useful to study the kinetics of secondary tissue development, where primary and secondary growths are temporally uncoupled. We here sought to demonstrate that the stem of adult hemp plants is an additional suitable model to study the heterogeneous lignification of the tissues and the mechanisms underlying seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…RT-qPCR analyses were performed in 384-well plates on a ViiA7 Real-Time PCR System (Applied Biosystems) with the Takyon SYBR Green low ROX (Eurogentec). The primers were designed and validated as described (Behr et al 2018a) and the primer list can be found in the same manuscript. The sequences used for primer design are given in Supplementary Document S1.…”
Section: Rt-qpcrmentioning
confidence: 99%
“…RT-qPCR analyses were performed in 384-well plates on a ViiA7 Real-Time PCR System (Applied Biosystems) with the Takyon SYBR Green low ROX (Eurogentec). The primers were designed and validated as described (Behr et al 2018a) and the primer list can be found in the same manuscript. The sequences used for primer design are given in Supplementary Document S1.…”
Section: Rt-qpcrmentioning
confidence: 99%
“…Emperor of Lsat_1_v5_gn_5_140040 has on tipburn incidence; however, the cell wall could play a role in tipburn incidence by acting as a sink for Ca 2+ or influencing cellular integrity. Lsat_1_v5_gn_5_135361 encodes for β-galactosidase 2 (BGAL2), which has been shown to be important in secondary cell wall formation in flax ( Linum usitatissinum ) and hemp ( Cannabis sativa ; Roach et al 2011 and Behr et al 2018 ). However, Moneo-Sánchez et al (2018) studied knockout mutants of several BGAL genes and found no significant phenotypic changes, which lead them to conclude that other β-galactosidases from the same subfamily can compensate for the loss of function of these proteins.…”
Section: Discussionmentioning
confidence: 99%